Endobronchial metastases from melanoma: a survival analysis. (25th February 2016) - Chaussende, Amandine; Hermant, Christophe; Tazi‐Mezalek, Rachid; Favrolt, Nicolas; Hureaux, José; Fournier, Clément; Lorut, Christine; Paganin, Fabrice; Ngo, Minh‐Triet; Vandemoortele, Thomas; Anevlavis, Stavros; Froudarakis, Marios E.; et al.
Abstract: Background: Metastatic spread to the tracheobronchial tree from other than bronchopulmonary tumors is a common clinical problem. However, malignant melanoma, a highly metastatic potential tumor, is rarely metastasing in the airways. Therefore little is known about survival of patients with endobronchial metastasis from melanoma. Objectives: The aim of our study was to assess survival of patients with endobronchial metastasis of melanomas according to clinical and radiological features, to determine any possible factor affecting survival. Methods: This retrospective study included 19 patients who underwent a bronchoscopy from 11 different hospitals. Data about patients' demographics, symptoms, radiographic, endoscopic findings and treatment were investigated to evaluate any possible impact on survival. Results: Endobronchial metastases occurred at a median of 48 months (range 0–120) following the diagnosis of the primary tumor. About 73.7% of patients had other proven metastases when the endobronchial involvement was diagnosed. Symptoms are not specific as well as radiological features. Median overall survival of the studied population was 6 months (range 1–46). Factors of poor survival were multiple metastatic sites ( P = 0.019), pleural ( P = 0.0014) and soft tissue metastasis ( P = 0.024). Different treatment modalities applied in our patients showed no effect on survival. Conclusion: Patients with endobronchial metastasis have overall poor survival, affected by multiple organ involvement, the presence of pleural and soft tissue disease, while no impact on survival has been shown by any treatment applied.